Porcine respiratory disease complex: Dynamics of polymicrobial infections and management strategies after the introduction of the African swine fever - Assavacheep, Pornchalit; Thanawongnuwech, Roongroje (Frontiers in Veterinary Science, 2022)
A few decades ago, porcine respiratory disease complex (PRDC) exerted a major economic impact on the global swine industry, particularly due to the adoption of intensive farming by the latter during the 1980s. Since then, the emerging of porcine reproductive and respiratory syndrome virus (PRRSV) and of porcine circovirus type 2 (PCV2) as major immunosuppressive viruses led to an interaction with other endemic pathogens (e.g., Mycoplasma hyopneumoniae, Actinobacillus pleuropneumoniae, Streptococcus suis, etc.) in swine farms, thereby exacerbating the endemic clinical diseases. We herein, review and discuss various dynamic polymicrobial infections among selected swine pathogens. Traditional management strategies including disease diagnosis (laboratory examinations and practical biosecurity through multisite production, parity segregation, batch production, and the adoption of all-in all-out production systems) and specific vaccination and medication protocols for the prevention and control (or even eradication) of swine diseases are also discussed. After the introduction of the African swine fever (ASF), particularly in Asian countries, new normal management strategies minimizing pig contact by employing automatic feeding systems, artificial intelligence (AI), and robotic farming and reducing the numbers of vaccines required, may more or less lead to the re-emergence of existing swine pathogens (PRRSV or PCV2) or could somehow facilitate the elimination of some pathogens after the ASF-induced depopulation. ASF-associated reborning strategies are, therefore, essential for the establishment of food security. The “reborn swine farm” policy and the strict biosecurity management (without the use of ASF vaccines) are, herein, discussed for the sustainable management of small-to-medium pig farms, as these happen to be the most potential sources of an ASF re-occurrence. Finally, the ASF disruption has caused the swine industry to rapidly transform itself. Artificial intelligence and smart farming have gained tremendous attention as promising tools capable of resolving challenges in intensive swine farming and enhancing the farms’ productivity and efficiency without compromising the strict biosecurity required during the ongoing ASF era.